Configuration of the Values of Al-Qur’an, Pancasila, and Mathematics: Critical Study of Integration-Based Analysis in Indonesia - Wahidah, Evita Yuliatul; Abdillah, Syaik; Sahroni, Roni; Sirait, Sangkot; Kusumaputri, Erika Setyanti (LPPM IAIN Kudus, 2023)
This paper presents about the values of Al-Qur’an, Pancasila, and Mathematics in the discourse on the theory of interconnection integration undergoing a demystification process. The configuration of the values of Al-Qur’an, Pancasila, and Mathematics through Islamic studies is carried out with a theo-anthropocentric process on the integralist values of Al-Qur’an to Mathematics, giving birth to six models, namely Mathematics for Al-Qur’an, Mathematics from Al-Qur’an, Mathematics to explore Al-Qur’an, Mathematics to deliver Al-Qur’an, Mathematics to explain Al-Qur’an, and Mathematics with Al-Qur’an. In integration, there is an effort to restructure Qur’anic and Mathematical sciences, while in interconnection there are meetings in the format of complementation, comparison, confirmation, and the contribution of the verses of Al-Qur’an to the five precepts of Pancasila.